Improving the Stability of Subsurface Structures in Deep Metal Mines by Stress and Energy Adjustment: A Case Study. (21st April 2021) - Liu, Huanxin; Liu, Xingquan; Tan, Zhuoying; Liu, Yang; Li, Guilin
Abstract : In deep hard-rock mines, the failure of subsurface structures (e.g., tunnels, stopes, and shafts) has been a significant problem affecting mining safety due to the high-stress environment. In this paper, the mechanism of structural failure and instability is discussed, and optimized excavation methods are proposed for stress control in deep gold mines. Based on the field observation and investigation of the joints distribution and rock failure modes at 800–1200 m depth of several large gold mines and a typical ultradeep borehole (2017 m depth) in northwest Jiaodong Peninsula, three engineering methods for reducing stress, including the stress transferring by mining optimizations, pressure relief by boreholes, and energy release in advance by optimizations of excavation and support, are analyzed by numerical simulation and field monitoring. Results show that stress reduction by excavation alone is limited and the backfill mining method is more conducive to stress transfer than the opening stope method. Roof contacted backfill can produce an unloading zone around the stope and reduce the stress of the surrounding stope. Relief boreholes can reduce the stress concentration of stopes, but the effect of cutting seams generated by presplitting blasting on pressure relief is not significant. The technology "short excavation and short support" releases less energy. By increasing the bench height and the reasonable timing of support by calculating, the elastic strain energy of rock in the shaft is prereleased, which benefits the long-term stability of the shaft.